GcType: a high-quality type strain genome database for microbial phylogenetic and functional research. Issue Volume 49:Issue D1(2021) (29th October 2020) - Shi, Wenyu; Sun, Qinglan; Fan, Guomei; Hideaki, Sugawara; Moriya, Ohkuma; Itoh, Takashi; Zhou, Yuguang; Cai, Man; Kim, Song-Gun; Lee, Jung-Sook; Sedlacek, Ivo; Arahal, David R; et al.
Abstract: Taxonomic and functional research of microorganisms has increasingly relied upon genome-based data and methods. As the depository of the Global Catalogue of Microorganisms (GCM) 10K prokaryotic type strain sequencing project, Global Catalogue of Type Strain (gcType) has published 1049 type strain genomes sequenced by the GCM 10K project which are preserved in global culture collections with a valid published status. Additionally, the information provided through gcType includes >12 000 publicly available type strain genome sequences from GenBank incorporated using quality control criteria and standard data annotation pipelines to form a high-quality reference database. This database integrates type strain sequences with their phenotypic information to facilitate phenotypic and genotypic analyses. Multiple formats of cross-genome searches and interactive interfaces have allowed extensive exploration of the database's resources. In this study, we describe web-based data analysis pipelines for genomic analyses and genome-based taxonomy, which could serve as a one-stop platform for the identification of prokaryotic species. The number of type strain genomes that are published will continue to increase as the GCM 10K project increases its collaboration with culture collections worldwide. Data of this project is shared with the International Nucleotide Sequence Database Collaboration. Access to gcType is free at http://gctype.wdcm.org/ .